How agro-environmental and climate measures are affecting farming system performances in Guadeloupe?: Lessons for the design of effective climate change policies - Audrey Fanchone; Laetitia Nelson; Nastassja Dodet; Luc Martin; Nadine Andrieu (International Journal of Agricultural Sustainability, 2022)
Relatively a few studies assess the impact of climate change (CC) policies on effective farmers’ agronomic practices and associated agro-technical performance. This study aimed at characterizing how CC policies can help farmers to combine CC with other environmental issues to support the design of more effective policies at the farm level. It was conducted in Guadeloupe, where farming systems are highly vulnerable to CC. We analyzed the Agro-Environmental and Climate Measures (AECM) proposed by the European Union. We made surveys with 39 farmers and used an existing whole-farm simulation tool to assess practices promoted by the current AECM. The tool was also used to assess the new AECM under discussion by stakeholders. Structural characteristics allowed identifying various types of farms. These characteristics may affect farmers’ capacity to implement the current AECM given that they are labour-intensive. New AECM focused on the decrease in pesticides and do not properly address CC since most of them lead to an increase in greenhouse gas emissions and are very different from the current farmers’ CC adaptation strategies. Synergies can be found between the reduction of pesticide use and CC if the alternatives proposed also permit to decrease in the use of synthetic fertilizers.